Late Pleistocene Eifel eruptions: insights from clinopyroxene and glass geochemistry of tephra layers from Eifel Laminated Sediment Archive sediment cores. (8th August 2019) - Förster, Michael W.; Zemlitskaya, Anastasia; Otter, Laura M.; Buhre, Stephan; Sirocko, Frank
ABSTRACT: The Eifel Laminated Sediment Archive (ELSA), which comprises several cores from maar lakes, includes numerous tephra layers spanning the last 140 000 years. The sediment cores are dated by 14 C and thermoluminescence as well as tuned to Greenland stadial–interstadial successions. Within the last glacial cycle, the Eifel Volcanic Fields are source to several widespread tephra layers, namely the Laacher See, Eltville, Rambach and Rocourt Tephra. However, a corresponding source volcano was so far only identified for the Laacher See Tephra. In this study we use glass and clinopyroxene geochemistry to link the remaining tephra layers to possible eruption centers within the West and East Eifel Volcanic Fields: while we demonstrate that the Eltville Tephra originated from an earlier eruption of the Laacher See Volcano at 24 300 a bp from within the East Eifel Volcanic Field, the Rambach and Rocourt Tephras are sourced from the West Eifel Volcanic Field and erupted from Wartgesberg at 27 900 a bp and Pulvermaar at 75 000 a bp, respectively. Phases of volcanic activity peaked at 10 000–30 000 and 60 000–80 000 a bp and were thus erupted around the temperature minima of the last glacial cycle. The longest phase of dormancy between individual vents was around 30 000 years long, within the last interglacial.